Компенсація параметричної несиметрії асинхронного двигуна при його живленні від частотно-регульованого електропривода - Чумачова, А.В.; Калінов, А.П. (Технічна електродинаміка, 2012)
The paper justificates the expressions to identify the corrective voltage for compensation of the variable components of the induction motor active power and electromagnetic torque, which caused by stator phases asymmetry.